3D Marine Cadastral System to Support Marine Spatial Planning Implementation in Indonesia: A Case Study of Penanjung Bay, Indonesia - Kurniawan, Agung; Pranowo, Widodo Setiyo; Hardjo, Karen Slamet; Santoso, Agus Iwan; Khakhim, Nurul; Purwanto, Taufik Hery; Setiyadi, Johar (Geomatics and Environmental Engineering, 2023)
The ocean is a formation that has a volume and consists of a surface layer of water, a column, and a bottom. Visualization of the sea on a digital map is important to support the acceleration of marine spatial planning (MSP), which is generally two-dimensional on a flat plane. A marine cadastre is defined as an instrument used in managing spatial boundaries, which describes, visualizes, and realizes legally defined boundaries as well as rights, restrictions, and responsibilities related to activities in the marine environment. Therefore, visualization in 3D will open a wider perspective than conventional maps. The 3D marine cadastral system was built using the Penanjung Bay pilot project and the QGIS2ThreeJS plugin with JavaScript. The results obtained can provide a 3D visualization of the position and boundaries for each component of the marine cadastre in Penanjung Bay with a broader picture of the sea spatial layout in the region.